2018
DOI: 10.1093/ptj/pzy090
|View full text |Cite
|
Sign up to set email alerts
|

Association of Muscle Strength and Walking Performance in Adult Patients With Pompe Disease

Abstract: BackgroundThe loss of the ability to walk is among the most prominent signs of Pompe disease. The associations with muscle strength have not been described.ObjectiveThe objective of this study was to estimate the associations of walking performance with muscle strength in 4 specific lower extremity muscle groups along with other factors in adult patients with Pompe disease.DesignThis was a single-center, cross-sectional study.MethodsMuscle strength (hand-held dynamometry of hip flexion and abduction and knee e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…There is some evidence to suggest that females are likely to have better walking performance compared to males (i.e. a higher proportion of females walk with a more typical gait) (Favejee et al, 2018) however, this was crosssectional study and therefore would be difficult to draw predictive conclusions. To our knowledge there is limited evidence exploring differences in strength and walking characteristics between males and females who are diagnosed with LOPD.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…There is some evidence to suggest that females are likely to have better walking performance compared to males (i.e. a higher proportion of females walk with a more typical gait) (Favejee et al, 2018) however, this was crosssectional study and therefore would be difficult to draw predictive conclusions. To our knowledge there is limited evidence exploring differences in strength and walking characteristics between males and females who are diagnosed with LOPD.…”
Section: Discussionmentioning
confidence: 95%
“…Future research should explore the lumbar spine posture and motion during walking. indicates exercise tolerance (Chetta et al, 2006;Gibbons, Fruchter, Sloan, & Levy, 2001) and has shown to reduce with the progression of late-onset Pompe disease in association with reduced strength and respiratory capacity (Favejee et al, 2018;Schüller et al, 2012;Wokke et al, 2008). Furthermore, inclusion criteria for LOPD patients in this study required individuals to be able to walk unaided for 50 m. However, McIntosh et al (2015) recruited individuals who were able to walk at least 10 m with or without a walking aid, with 50% of participants using a walking aid during their study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations